Sociotechnical Perspective on Implementing Clinical Video Telehealth for Veterans with Spinal Cord Injuries and Disorders - Martinez, Rachael N. (Telemed J E Health, 2017)
Background: Real-time videoconferencing technology such as clinical video telehealth (CVT) offers a means to reach patient populations who face limited access to healthcare. The Veterans Health Administration has invested in CVT to improve care access for U.S. military veterans with spinal cord injuries and disorders (SCI/D); however, no studies have assessed the factors that influence implementation of this technology in clinical practice for individuals with SCI/D. Introduction: Guided by a sociotechnical perspective, the purpose of this study was to identify factors that influence implementation of CVT for veterans with SCI/D. Materials and Methods: We conducted semistructured telephone interviews with 40 healthcare providers who use CVT to deliver services to veterans with SCI/D. Results: Factors related to workflow and communication were widely reported as implementation barriers. Coordinating logistics for CVT appointments was challenging, and effective communication between CVT team members across facilities was considered crucial. Providers also cited factors related to technical infrastructure, people, and organizational features, including the need for appropriate equipment, space, personnel, and support for using CVT equipment. Discussion: The implementation of CVT in the care of veterans with SCI/D was influenced by an interrelated set of social and technical factors. Key among them were social factors related to people, workflow, and communication, given that CVT supports healthcare teams interacting remotely in real time. Conclusions: CVT implementation requires teams working together to negotiate a complex, distributed process across multiple sites. Such complexity places a premium on teamwork and communication among healthcare teams before, during, and after a CVT encounter.